Pressure-induced chemical reordering in supercooled polyionic sulfophosphate liquids - Rodrigues, Bruno P.; Sen, Sabyasachi; Wondraczek, Lothar (Journal of Non-Crystalline Solids, 2018)
In situ pVT analyses of poly-ionic Na-Zn sulfophosphate liquids and glasses are carried out in conjunction with ex situ structural characterization using Raman and multi-nuclear (31P and 23Na) NMR spectroscopy. These ionic liquids exhibit highly homogeneous compaction behavior even close to their densification limit. With proceeding densification, no changes are seen on short-range order, however, both the increasing substitution of phosphate by sulfate and the high-pressure, high-temperature treatments show structural and thermodynamic indications of increasing chemical immiscibility, with the sodium ions preferring to surround the sulfate groups while the zinc ions prefer to neighbor the phosphate groups. It appears that such non-random cation distribution and its enhancement by structural compaction facilitates the densification behaviour of ionic glasses.
CRIS-Team Scopus Importer:2023-04-20